Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Les données linguistiques pour la recherche et la planification en santé : possibilité et limites pour l'étude des francophones en situation minoritaire - Bouchard, Louise; Lizotte, Mathieu (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Malgré de remarquables avancées de recherche sur la problématique de la santé en contexte francophone minoritaire, la disponibilité de variables linguistiques complètes et cohérentes dans les bases de données nationales de santé demeure lacunaire et fragmentée, constituant un défi considérable pour l’étude de la santé des membres des communautés francophones en situation minoritaire (CFSM) et la planification de services adaptés à cette population dispersée. Cet article offre un bilan exhaustif des possibilités et des limites des données disponibles permettant l’étude de la santé des CFSM. Ce faisant, il met en lumière une série de problèmes méthodologiques, dont le manque de données pertinentes, l’absence de variables standardisées et les faibles effectifs pour l’analyse régionale, entre autres. Ces lacunes entravent considérablement la capacité des chercheuses et chercheurs à étudier les conditions et les besoins spécifiques des CFSM en ce qui concerne la santé et la planification de la santé. Mots-clés : données linguistiques, problèmes méthodologiques, francophone, minorité, quantification

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

La mobilisation des connaissances en santé dans les CFSM [infographie] - Consortium national de formation en santé (2021)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

La mobilisation des connaissances en santé dans les petites communautés francophones en situation minoritaire. Ses défis, ses conditions de succès - Johnson, Marc. L.; Cimon, Virginie; Dancause, Luc; Forest, Mariève (SOCIUS recherche et conseils, 2021)

Health Data for Linguistic Minority Group Research in Canada: Proof-of-Concept Centralized Health Care Metadata Repository Development and Usability Study - Martin-Schreiber, Vincent; Peixoto, Cayden; Batista, Ricardo; Belanger, Christopher; Tanuseputro, Peter; Hsu, Amy T; Bjerre, Lise M (JMIR Infodemiology, 2026)
Background Language barriers between Canadian patients and health care providers are associated with poorer health outcomes, including decreased patient safety and quality of care, misdiagnosis and longer treatment initiation times, and increased mortality. However, research exploring language as a social determinant of health is limited, as Canadian health data are scattered across many jurisdictions, each with its own policies and procedures. This fragmentation makes it difficult for researchers to identify, locate, and use existing data. This paper presents the results of a pilot study that attempts to address this gap by creating a metadata repository (MDR) to act as a central source of information about what data are available at which data holdings across Canada. Objective This project aimed to (1) create a proof-of-concept MDR for Canadian health data at the variable level; (2) identify and label language-related variables existing within the MDR data; and (3) develop an interactive, public-facing web application to let users browse and search the MDR. Methods Metadata were collected from 5 Canadian health data sources, including 4 provincial data holdings and 1 national survey, and pooled to create a data repository. Then, we performed bottom-up labeling of language-related variables within the pooled metadata by first using a search string algorithm across all variable labels, names, and definitions and then consensus screening these variables using a derived, standardized definition of language or linguistic variables. Using the Shiny web framework in R, we then developed an openly accessible web application to allow users to search the proof-of-concept MDR. Results A total of 850,343 variables were collected and included in the repository, with most coming from Ontario (n=712,037, 83.7%) and Manitoba (n=97,051, 11.4%) provincial data holdings. Among all variables in the repository, 213,696 (25.1%) were confirmed to be language related. Conclusions Developing a national MDR would be a transformative opportunity for Canadian researchers to leverage the full scope of Canadian health administrative data. Although a top-down approach with consistent engagement of and collaboration between provincial data holdings and federal data agencies is ideal to develop a national MDR, this study demonstrates the feasibility of a bottom-up approach in contributing to this overarching goal.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Obligations linguistiques et recherche en santé : analyse du rapport des IRSC aux communautés francophones en situation minoritaire - Pelbois, Christelle; Bouchard, Louise (Minorités linguistiques et société, 2026)
Le Canada compte deux langues officielles, mais la recherche en santé menée sur et par les communautés francophones en situation minoritaire demeure fragilisée par l’anglicisation. Cet article analyse les dynamiques sociales qui structurent cette recherche et les tensions entre exigences d’excellence scientifique et reconnaissance de sa légitimité. Le cas des Instituts de recherche en santé du Canada, visés par une enquête du Commissariat aux langues officielles, illustre les limites actuelles du soutien institutionnel. La récente modernisation de la Loi sur les langues officielles qui reconnaît l’inégalité de statut des langues et les besoins différenciés, ouvre toutefois des perspectives d’équilibrage. Canada has two official languages, yet health research conducted by and on Francophone minority communities remains vulnerable to the effects of anglicization. This article examines the social dynamics shaping this research and the tensions between scientific excellence requirements and recognition of its legitimacy. The case of the Canadian Institutes of Health Research (CIHR), subject to an investigation by the Office of the Commissioner of Official Languages, highlights current institutional shortcomings. The recent modernization of the Official Languages Act, which acknowledges the unequal status of languages and differentiated needs, nonetheless opens new opportunities to rebalance these dynamics.

Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2020)

Framework for the Analysis of Health and Social Services Access and Integration for Official Language Minority Communities - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2020)